Városfejlődés és banki infrastruktúra: Városhierarchia vizsgálatok a pénzintézeti innovációk elterjedése alapján a XX. századi Magyarországon - Gál, Zoltán (Tér és Társadalom, 1996)
This essays covers a few issues of the connection of urban development and the banking system in the urban network of Hungary on the turn of the 20th century. The basic concept of the survey was a statement of the American geographical school which says that the features of the urban network are in a tight correlation with the spatial structural processes of the innovation of financial institutes. During the past 150-200 years, the role of the towns in economy, society and culture has extremely increased. Researches which consider the unity of spatial and temporal analyses as of great importance and give a new dimension to historical geographical analyses, find it necessary to examine the hierarchic system of the urban network that stands out from the regional frameworks. The comparative analysis of the urban network in Hungary is given a special significance by the fact that in this region the characteristic features of modernisation and bourgeois development almost exclusively took place at the levei of the city centres in the beginning of this century.